Research Involving Children. Children?s School Image - Zwiernik, Jolanta (INSTED: Interdisciplinary Studies in Education & Society, 2017)
The aim of the text is to reflect on the conceptualisation and status of research, which involves children. The article consists of two parts. The first one includes a comparative analysis of the specifics and conditions of research conducted with children and adults. The second part presents research results, where children were involved (interview and ethnographic observation) that bring the researcher closer to discover the school image from their own perspective. The conclusion indicates the necessity of reflective location of children research on a continuum ? from the very similar to those which are carried out with adults.